Strategi Marketing Communication Seca Sebagai Brand Lokal dalam Membangun Brand Awareness (representamen, 2023)
Seca is a newcomer as a local skincare brand that has a strategy to build brand awareness so that its products can be the choice of consumers in the midst of competition from other local facial skincare brands. The purpose of this research is to find out Seca's marketing communication strategy as a local brand in building brand awareness. The theory used in this research is the Integrated Marketing Communication (IMC) theory from Firmansyah. This research uses post- positivism paradigm with descriptive qualitative research method. The subjects is the Seca brand management team. Objects in this research are marketing communication strategy of Seca as a local brand in building brand awareness. Primary data collection techniques in this research used semistructured interviews with key informants and informants and non- participatory observation. Secondary data collection by library study and documentation. The result of this research shows that Seca has implemented marketing communication strategy using IMC theory by emphasizing on advertising strategy and e-word of mouth marketing through KOL to build brand awareness. Through these strategies, Seca is currently at the brand recognition level in the brand awareness pyramid. Keywords: Brand Awareness, Marketing Communication, Seca, Strategy.